A Legal Allusion: The Correlation of Law and History in Ezekiel 20. - Jarrard, Eric X. (Vetus Testamentum, 2023)
This article expands the well-established relationship between Ezek 20 and the Holiness Code (H), developed by, among others, Michael Lyons. I argue that Ezekiel articulates the relationship between the exodus event and the legal material using an extensive intertextual allusion to H. These connections enable us to appreciate more thoroughly Ezekiel's historiographical project, as well as exposing possible Deuteronomic redaction of the chapter that assumes and utilizes the established time patterning of the surrounding verses. The article concludes with a reflection on the mnemonic activity in Ezek 20 regarding how the chapter uses (proto-) Lev 18–20 to advocate for the preeminence of legal material and especially H in patterning time and conceptions of the exodus for future generations.